The Effect of MicroRNA 21 and MicroRNA 200b Expression on Carcinogenesis in Endometriosis-Associated Ovarian Cancers and Relationship with Clinicopathological Parameters - Esra Canan Kelten Talu; Emine Çağnur Ulukuş; Yasemin Çakır; Merih Güray Durak; Zeynep Bayramoğlu; Hikmet Tunç Timur; Sefa Kurt; Sefai Merve Özdemir; Safiye Aktaş (Medicina)
(1) Background and Objectives: Endometriosis is defined as the presence of endometrial glands and stroma outside the uterine cavity. It affects 5–15% of women of reproductive age. Ovarian cancer develops in approximately 1% of patients with endometriosis. Prediction of those with endometriosis who will develop ovarian cancer is among the current research topics. (2) Materials and Methods: With this study, we aimed to reveal the role of miRNA 200b and miRNA 21 in endometriosis-associated ovarian carcinoma (EAOC). Thirteen patients diagnosed as having EAOC between 2015 and 2023 were included, with their endometriosis and eutopic endometrium tissues (Group 3: 13 patients, 39 tissue samples). Two separate groups were then detected to compare with these cases: Group 2 composed of tuba-ovarian endometriosis with its eutopic endometrium (10 patients, 20 tissue samples) and Group 1 composed of eutopic endometrium only (10 patients, 10 tissue samples). The foci marked on H&E sections were determined from the area on the relevant paraffin blocks and small tissue samples were taken in tubes to be studied with real-time PCR. (3) Results: No significant difference was detected for miRNA 21 and miRNA 200b expression levels among eutopic endometrium, endometriosis, and cancer foci in Group 3. However, miRNA 21 and miRNA 200b expression levels in the eutopic endometrial tissue of cases with ovarian cancer were significantly higher than in the eutopic endometrial tissues of cases with (Group 2) and without endometriosis (Group 1). (4) Conclusions: This study suggests that increased miRNA 200b and miRNA 21 expression levels detected in eutopic endometrial tissue of patients with endometriosis may contribute to identifying cases that may develop EAOC.